Maternal risk of chronic energy deficiency based on mid-upper arm circumference and low birth weight among term singleton births: A retrospective record-based study in Lampung, Indonesia - Lara Putri Upatesa; Anita Anita; Rilyani Rilyani (Lentera Perawat, 2026)
Background: Low birth weight remains a major neonatal health concern. Mid-upper arm circumference (MUAC) is routinely used in Indonesia to screen pregnant women for risk of chronic energy deficiency (CED), but its association with low birth weight among term births requires careful interpretation. Objective: To examine the association between maternal risk of CED based on antenatal MUAC and low birth weight among term singleton births at Dr. H. Abdul Moeloek Regional General Hospital, Lampung, Indonesia. Methods: This retrospective record-based analytic study included 93 term singleton mother-infant pairs selected consecutively from 178 eligible delivery records from January to August 2025. Maternal risk of CED was defined as the most recent documented antenatal MUAC <23.5 cm; MUAC >=23.5 cm was classified as not at risk. Low birth weight was defined as birth weight <2,500 g. Sample adequacy was reassessed using a single-proportion approach with 95% confidence, an expected proportion of 0.50, 7.5% precision, finite-population correction, and 5% allowance for incomplete records, producing a minimum of 92 records. Pearson chi-square and crude odds ratio (OR) with 95% confidence interval (CI) were calculated. Results: Forty infants (43.0%) had low birth weight, and 20 mothers (21.5%) were at risk of CED. Low birth weight occurred in 18 of 20 mothers at risk of CED (90.0%) and in 22 of 73 mothers not at risk (30.1%). Maternal risk of CED was associated with low birth weight (p < 0.001; crude OR = 20.864; 95% CI = 4.455-97.718). The wide CI indicates substantial uncertainty in the magnitude of the estimate. Conclusion: Maternal risk of CED based on MUAC was associated with low birth weight among term singleton births. The finding supports consistent antenatal MUAC screening, but it should be interpreted as an unadjusted hospital-based association that requires confirmation in larger studies with standardized MUAC timing and multivariable adjustment.